Views on Capitalism in the Pre-War Works of A. Maceina and P. Jakas - Pruskus, Valdas (Problemos, 1986)
A. Maceina’s and P. Jakas’s, Lithuanian bourgeois Catholic modernists, views on capitalism are considered. In the author’s opinion, they have disclosed real contradictions and problems of capitalism, and the dehumanizing nature of the main law of capitalistic production, that is, of the law of production of surplus value. Nevertheless, they understood the law not as an objective consequence of, definite class-relations, but as a purely idealistic manifestation of the “capitalist spirit” in man, that is, as a fact of man’s consciousness, regulating the whole production. Thus they have ignored objective regularities of the development of capitalism.